Effect of Workload And Work Stress On The Work Quality Of Employees Of BPBD, North Luwu District - Wanda, Wanda; Kusdarianto, Indra; Patra, A. Dahri Adi (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
urpose: This study aims to examine the influence of workload and work stress on the work quality of employees at the Regional Disaster Management Agency (BPBD) of North Luwu Regency. Methodology: The research employs a quantitative approach using a saturated sampling technique involving 55 employees. Data were collected through structured questionnaires and analyzed using multiple linear regression supported by classical assumption tests. Results: The findings indicate that workload and work stress simultaneously have a significant effect on employee work quality, with a coefficient of determination of 46.7%, suggesting that nearly half of the variation in work quality is explained by these variables. Novelty: This study provides empirical evidence on the combined impact of workload and work stress within a public-sector disaster management institution. Findings: Excessive workload and unmanaged work stress negatively affect employee work quality, highlighting the need for effective workload distribution and stress management. Originality: The originality of this study lies in its focus on BPBD employees in a regional disaster management context, which remains underexplored in prior research. Conclusions: Proper management of workload and work stress is essential to enhance employee work quality and organizational performance. Type of Paper: Empirical Research Paper.